2022
DOI: 10.56225/ijfeb.v1i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Can Sharia Finance Affect Indonesia’s Economic Growth?

Abstract: This study determines the effect of sharia bank financing, sharia mutual funds, sharia shares and Sukuk on Indonesia's economic growth in the long and short term and analyzes the balanced relationship between the independent variable and the dependent variable using the ARDL method. Stationarity testing using the Augmented Dickey-Fuller Stationary (ADF) approach, from March 2011 to September 2021. The results found that the long-term estimation of Sukuk has a positive and significant effect on economic growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
3
1
0
1
Order By: Relevance
“…Conversely, the empirical findings of Yüksel and Canöz (2017) indicate that there is no cointegration between Islamic banking and economic growth. Same results were found by Fuadi et al (2022) in Indonesia where Islamic banking finance could not significantly influence economic growth, so they are supporting neutrality hypothesis. Khaliq and Thaker (2017) argued that Islamic banking and finance play a prominent role in driving the economic development of Malaysia.…”
Section: Islamic Banking and Economic Growthsupporting
confidence: 70%
See 3 more Smart Citations
“…Conversely, the empirical findings of Yüksel and Canöz (2017) indicate that there is no cointegration between Islamic banking and economic growth. Same results were found by Fuadi et al (2022) in Indonesia where Islamic banking finance could not significantly influence economic growth, so they are supporting neutrality hypothesis. Khaliq and Thaker (2017) argued that Islamic banking and finance play a prominent role in driving the economic development of Malaysia.…”
Section: Islamic Banking and Economic Growthsupporting
confidence: 70%
“…Recently, Naz and Gulzar (2022b) discovered the stimulating effect of Sukuk on economic growth of Islamic countries in the long run. Relatedly, Fuadi et al (2022) also found that in the long run, Sukuk has a significant positive impact on economic growth of Indonesia, thus supporting supply leading hypothesis. The research of Yıldırım et al (2020) tested the relationship of Sukuk market and economic growth in nine Muslim countries, where Islamic financial system prevails.…”
Section: Islamic Bond and Economic Growthsupporting
confidence: 63%
See 2 more Smart Citations
“…Hal ini dapat dilihat pada literasi keuangan di Indonesia masih tergolong rendah. Menurut survei Otoritas Jasa Keuangan (OJK) pada 2022, indeks literasi keuangan nasional berada di angka 49,86% (Fuadi, Suriani, and Zulham 2022). Artinya, hanya sekitar separuh penduduk Indonesia yang memiliki pengetahuan memadai tentang produk dan layanan keuangan.…”
Section: Pendahuluanunclassified